2013
DOI: 10.1002/cjce.21950
|View full text |Cite
|
Sign up to set email alerts
|

Lattice boltzmann method for natural convection with multicomponent and multiphase fluids in a two‐dimensional square cavity

Abstract: A lattice Boltzmann method for natural convection with multicomponent and multiphase fluids in a two‐dimensional square cavity is presented. The model combines a multicomponent and multiphase method with a passive‐scalar approach, which is extended to be available for multicomponent immiscible flow in this paper. It has a good computational efficiency. The natural convection of flow with two of the same immiscible fluids are simulated using the model, and the agreement with the literature data is satisfactory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The variation of isotherms indicates the change of the dominant heat transfer mechanism from conduction to convection. This outcome is in agreement with the results of natural convection in a cavity domain which was investigated in previous studies [33]. Fig.…”
Section: Density Ratio |Gf|supporting
confidence: 93%
See 3 more Smart Citations
“…The variation of isotherms indicates the change of the dominant heat transfer mechanism from conduction to convection. This outcome is in agreement with the results of natural convection in a cavity domain which was investigated in previous studies [33]. Fig.…”
Section: Density Ratio |Gf|supporting
confidence: 93%
“…It is obvious that the LBE method is valid only for the incompressible limit u/c s → 0. This means that u is smaller than 0.13 [31,33]. In our simulation, to maintain a higher accuracy, maximum velocity needs to be smaller than 0.6 with consideration of the velocity field influence on the field temperature.…”
Section: Single Component Multi-phases (Scmp) Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, simulations based on this model were restricted to those without phase change process. Qiu et al also studied multicomponent jet flow with heat transfer without phase change . To the best of the authors’ knowledge, little research has been reported on multicomponent multiphase fluids accompanied by phase change with heat transfer.…”
Section: Introductionmentioning
confidence: 99%